Biocalyptic imaginations in Japanese and Korean films: undead nation-states in I Am a Hero and Train to Busan. Issue 3 (3rd July 2019) - Kim, Jaecheol
ABSTRACT: The primary purpose of this essay is to survey the recent zombie craze in Northeast Asian films from Japan and South Korea. While the concept of the zombie may have originated in colonial Haiti, with its ghoulish images and supernatural lore, zombies were later imported to North America and reformulated as popular cultural entertainment by Hollywood. They are now flourishing in an East Asian cinematic context preserved in a globalized form. The films under investigation – I Am a Hero and Train to Busan – share similar cultural subtexts despite their incommensurable experiences of global capitalism in Asia and its latest ideological phase, neoliberalism. Both films critique the current neoliberal order and were nurtured by historical traumas experienced by both countries as well as the pandemic spread of viruses, both real and imaginary, that have ravaged the region. Nevertheless, the most prominent issue explored by Japanese and Korean zombie films is the continuity of society and its reproduction: as cultural artifacts of the neoliberal world, these films offer dystopian visions in which exploitation accelerates to such an extent that states cannot protect themselves against the viral and capitalist onslaught.